Interregional Inequality: A Case Study in Russia - Maslikhina, Veronika Yu. (International Journal of Economics and Financial Issues, 2016)
A dynamics analysis of interregional inequality in Russia during the period of 1994-2014 was conducted. The first Theil index, computed using the main productivity indicator of regional economy - the gross regional product per capita, was used to estimate inequality. Spatial inequality level, tendencies and structural features in Russia as a whole and in several Russian macro-regions (federal districts) were identified. The link between interregional inequality in Russia and economic growth was identified. Sharp polarization reasons of the Russian regional space were defined. State regional policy measures to mitigate interregional inequality were analyzed. Keywords: interregional inequality, region, Russia JEL Classifications: D63, O52, R1, R58